Nonspecific Regulation of the Number of Immunocompetent Cells Under the Influence of DT Toxoid in Children With Glomerulonephritis - Kostinov, Mikhail Petrovich; Akhmatova, Nelli Kimovna; Magarshak, Olga Olegovna; Vlasenko, Anna Egorovna; Polishchuk, Valentina Borisovna; Kostinova, Aristitsa Mikhailovna; Mashilov, Kirill Vadimovich (Frontiers in Immunology, 2021)
The study aimed to study the effect of revaccination against diphtheria and tetanus on the proliferation and differentiation of immunocompetent cells, the formation of specific antibodies, and the course of the disease in children with glomerulonephritis (GN). The study included 45 children with glomerulonephritis (GN) aged 5 to 15 years, in remission from 6 months up to 4 years. Of these, 25 children were revaccinated with DT toxoid (Diphtheria-Tetanus toxoid with reduced antigenic content) and 20 were in the control group (not vaccinated). The subpopulation structure of lymphocytes was studied in dynamics after 1-6-12 months by flow cytometry and IgG levels to diphtheria and tetanus were studied by ELISA. During the year, none of the patients had an exacerbation of GN or a concomitant disease. After revaccination with DT toxoid, a significant increase in IgG antibodies against diphtheria and tetanus was revealed, which persisted after 12 months - 7.5 [5.1-10.8] IU/mL (p <0.001) and 7.2 [4.8-10.7] IU/mL (p <0.001), respectively. In the post-vaccination period, a multidirectional change in the concentration of T-lymphocytes was noted: with an initially increased level, their percentage after revaccination with DT toxoid decreases from 83 (81-86) % to 78 (76-80)% after a month (p = 0.04) and up to 75 (69-79)% after 12 months (p<0.001). In the control group, such a decrease was not observed. A similar picture was observed for T-helpers, cytotoxic T-lymphocytes, and in patients with an initially low percentage of cytotoxic T-lymphocytes, on the contrary, its increase was noted (p<0.001), which is comparable with the value of this parameter in the group of children with initially normal value (H = 0.54, p = 0.76). The same patterns were observed in the change in the content of B-cells: one month after revaccination, the relative level of B-cells in patients with an initially lowered value increased (p = 0.02) and remained for 12 months (p<0.001). Revaccination with DT toxoid in children with GN not only does not cause undesirable changes in the system of immunocompetent cells but also has an immunomodulatory effect, which contributes to the favorable maintenance of the remission period of the disease.